PENGARUH SELF ASESSMENT SYSTEM DAN WITHHOLDING TAX SYSTEM TERHADAP OPTIMALISASI PENERIMAAN PAJAK PENGHASILAN PASAL 21 PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA CIBITUNG - Lintas; Erna (Fakultas Ekonomi Universitas Borobudur, 2023)
Taxes are the main source of state revenue and are the largest in the APBN. For this reason, taxes are a very important factor for state finances, especially to guarantee the continuous recovery of national development, in financing state spending, both for general financing purposes, and financing in the context of carrying out government functions. Besides that, revenue from the tax sector is a very potential source of funding because the government can collect funds appropriately through the collection or withholding of taxes based on applicable laws. Keywords: Self Assessment System, Withholding Tax System, Optimization Of Income Tax Revenue Article 21